2022
DOI: 10.1007/s13311-022-01250-7
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed-Focused Ultrasound Provides Long-Term Suppression of Epileptiform Bursts in the Kainic Acid-Induced Epilepsy Rat Model

Abstract: Focused ultrasound (FUS) has potential utility for modulating regional brain excitability and possibly aiding seizure control; however, the duration of any beneficial effect is unknown. This study explores the efficacy and time course of a short series of pulsed FUS in suppressing EEG epileptiform spikes/bursts in a kainic acid (KA) animal model of temporal lobe epilepsy. Forty-four male Sprague–Dawley rats were recorded for 14 weeks with EEG while software calculated EEG numbers of epileptiform spikes and bur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…In these model mice, ultrasound delayed the onset of status epilepticus (SE) and inhibited acute seizure activity ( 65 ). Chu PC and colleagues found that, in the KA-induced epilepsy mouse model, LITUS could reduce the occurrence of seizures, and the effects lasted as long as 7 weeks ( 66 ).…”
Section: Ultrasonic Stimulation In Central Nervous System Diseasementioning
confidence: 99%
“…In these model mice, ultrasound delayed the onset of status epilepticus (SE) and inhibited acute seizure activity ( 65 ). Chu PC and colleagues found that, in the KA-induced epilepsy mouse model, LITUS could reduce the occurrence of seizures, and the effects lasted as long as 7 weeks ( 66 ).…”
Section: Ultrasonic Stimulation In Central Nervous System Diseasementioning
confidence: 99%
“…Chronic epilepsy animal models have consistently demonstrated that FUS session effectively suppresses epileptic signals in kainic acid (KA) models for up to seven weeks. 2 Duration of any therapeutic effect is of additional importance. Patients would not be likely to submit to daily sonications for an indefinite period of time.…”
mentioning
confidence: 99%
“…Transcranial focused ultrasound (FUS) is a cutting-edge technology with the capability to precisely target deep brain tissue noninvasively while minimizing impact on adjacent regions . Recent studies have revealed that employing FUS to induce neuromodulatory effects holds promise in suppressing epileptiform discharges, thus offering potential for treating epilepsy . Several human clinical trials employing repeated FUS treatments for temporal lobe epilepsy (TLE) have been conducted, revealing promising therapeutic potential (see details in Supplementary Table 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations